Synthesis and Characterization of MnCo2O4 Cuboidal Microcrystals as a High Performance Psuedocapacitor Electrode - Krishnan, Syam G.; Mohd Hasbi, Ab. Rahim; Rajan, Jose (Elsevier Ltd, 2016)
Manganese cobaltite (MnCo2O4) is currently under screening as a high performance supercapacitor electrode owing to its high theoretical capacitance, improved electrical conductivity and long term cyclic stability. Herein, we report synthesis of MnCo2O4 cuboidal microcrystals using hydrothermal method and compare its performance with its flakes prepared by solid combustion process. Crystal structure, surface properties, and electrochemical properties of the flakes are studied using X-ray diffraction, gas adsorption, field emission scanning electron microscopy, cyclic voltammetry, galvanostatic charge–discharge cycling, and electrochemical impedance spectroscopy. The electrochemical properties of MnCo2O4 flakes synthesized using hydrothermal synthesis are superior to that synthesized using the solid combustion process. Electrochemical properties of the cuboidal microcrystals (∼specific capacitance, CS ∼600 F g−1 @ 0.5 A g−1) are superior to those synthesized by the combustion process (CS ∼128 F g−1) due to improved faradic utilization of active surface area, layered cuboidal morphology, faster OH− ion penetration owing to higher diffusion coefficient, and larger voltage range available for electrochemical reaction.